Marine Law and Policy for Scientists and Managers - Campbell, Holly V. (Open textbook library., 2019)
This open educational resource is designed for use by undergraduate and graduate ocean science, natural resource, fisheries and wildlife, and environmental policy students enrolled in a ten-week academic quarter. The purpose of this project is to provide students and non-law professionals with a freely accessible, clearly written guide to support engaging and effective learning. As such, the book serves as a gateway and an invitation to become a well informed, committed and involved ocean citizen as well as to explore the field beyond our course study.